504 - Periodontal Disease and Risk of Dementia in Medicare Patients with Hepatitis C Virus. (October 2021) - Malone, Joseph E.; Tran, Linh; Jung, Jeah; Zhao, Chen
Abstract : Objective: To examine whether periodontal disease increases the risk of developing Alzheimer's disease and related dementias (ADRD) among hepatitis C patients in Medicare claims data. Background: Periodontal disease and hepatitis C virus (HCV) represent chronic infectious statesthat are common in elderly adults. Both conditions have independently been associated with an increased risk for dementia. Chronic infections are thought to lead to neurodegenerative changes in the central nervous system possibly by promoting a proinflammatory state. This is consistent with growing literature on the etiological role of infections in dementia. No studies have evaluated the association of periodontal disease with dementia in HCV patients. Methods: We used Medicare claims data for HCV patients to assess the incidence rate of ADRDwith and without exposure to periodontal disease between 2014 and 2017. Diagnosis of periodontal disease, HCV, and ADRD were based on ICD-9 and ICD-10 codes. A Cox multivariate regression model was used to estimate the association between periodontal disease and development of ADRD, controlling for age, gender, race, ZIP-level income and education, and medical comorbidities. Results: Of the 440, 578 patients in the dataset, the incidence rate of ADRD in the periodontal disease group was higher compared to those without periodontal disease (10.77% vs. 9.27%, p<0.001, and those with periodontal disease developed ADRD earlier compared to those withoutperiodontal disease (1.15 vs. 1.78 years, p<0.001). The hazard of developing ADRD was 1.23 times higher in those with periodontal disease (95% CI, 1.19 to 1.27, p< 0.001) after adjusting for all covariates, including age. Conclusion: Periodontal disease increased the risk of developing ADRD in HCV patients in anational Medicare claims dataset.